∫ 0 1 ln x x 2 − 1 d x = ln a
The equation above holds true for positive integer a . What does a − 2 equal?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the integral ∫ 0 1 ln x x b − 1 d x = I ( b )
I ′ ( b ) = ∫ 0 1 d b d ( ln x x b − 1 ) d x
d b d ( x b − 1 ) = l n ( x ) x b
Therefore I ′ ( b ) = ∫ 0 1 x b d x
I ′ ( b ) = b + 1 x b + 1 t o x = 0 f r o m x = 1
I ′ ( b ) = b + 1 1
Taking the integral of both sides we reach;
I ( b ) = ln ( b + 1 ) + c
We know that ∫ 0 1 ln x x b − 1 d x = I ( b ) = ln ( b + 1 ) + c
Let b = 0
We get ∫ 0 1 ln x x 0 − 1 d x = I ( 0 ) = ln ( 0 + 1 ) + c
0 = ln ( 1 ) + c
c = 0
I ( b ) = ln ( b + 1 )
I ( 2 ) = ln ( 2 + 1 )
I ( 2 ) = ln ( 3 )
a = 3
a − 2 = 1
Alternatively to the differentiation under the integral sign technique, we can convert this to a double integral. Notice ∫ 0 2 x t d t = ln ( x ) x 2 − 1 . Let I denote the integral in question, we can rewrite I equivalently as I = ∫ 0 1 ∫ 0 2 x t d t d x and we can utilize Fubini's Theorem to interchange the order of integration to give I = ∫ 0 2 ∫ 0 1 x t d x d t which gives I = ∫ 0 2 t + 1 1 d t = ln ( 3 ) thus a − 2 = 1 .
Problem Loading...
Note Loading...
Set Loading...
Similar solution with @Will McGlaughlin 's
Let
I ( u ) ∂ u ∂ I ( u ) ⟹ I ( u ) I ( 0 ) ⟹ I ( u ) ⟹ I ( 2 ) = ∫ 0 1 ln x x u − 1 d x = ∫ 0 1 ln x ln x ⋅ x u d x = ∫ 0 1 x u d x = u + 1 1 = ∫ u + 1 1 d u = ln ( u + 1 ) + C = ln ( 0 + 1 ) + C = 0 = ln ( u + 1 ) = ln 3 where C is the constant of integration. Note that I ( 0 ) = 0 ⟹ C = 0
Therefore, a − 2 = 3 − 2 = 1 .